SOLOK CITY HERITAGE (SoCH) - Mellya Fitri (Akademi Pariwisata Bunda Padang, Sumatera Barat, Indonesia, 2021)
This article is motivated by the tourism potential, culture and creative economy that exist in Solok City. Unfortunately, it is still running independently. There is no collaboration yet. Therefore, this article aims to collaborate potentials (tourism, culture and creative economy) with academics, government, business, community / society, and the media (pentahelix) in order to increase the community's economy, reduce unemployment, alleviate poverty and increase the number of visits to the City of Solok. Some tourist attractions at SOLOK CITY HERITAGE (SoCH) are described to motivate any collaborations.